Reduced bone mineral density in men after heart transplantation - Anijar,J.R. (1999)
Heart transplantation is associated with rapid bone loss and an increased prevalence and incidence of fractures. The aim of the present study was to compare the bone mineral density (BMD) of 30 heart transplant (HT) recipients to that of 31 chronic heart failure (CHF) patients waiting for transplantation and to determine their biochemical markers of bone resorption and hormone levels. The BMD of lumbar spine and proximal femur was determined by dual-energy X-ray absorptiometry. Anteroposterior and lateral radiographs of the thoracic and lumbar spine were also obtained. The mean age of the two groups did not differ significantly. Mean time of transplantation was 25.4 ± 21.1 months (6 to 88 months). Except for the albumin levels, which were significantly higher, and magnesium levels, which were significantly lower in HT patients when compared to CHF patients, all other biochemical parameters and hormone levels were within the normal range and similar in the two groups. Both groups had lower BMD of the spine and proximal femur compared to young healthy adults. However, the mean BMD of HT patients was significantly lower than in CHF patients at all sites studied. Bone mass did not correlate with time after transplantation or cumulative dose of cyclosporine A. There was a negative correlation between BMD and the cumulative dose of prednisone. These data suggest that bone loss occurs in HT patients mainly due to the use of corticosteroids and that in 30% of the patients it can be present before transplantation. It seems that cyclosporine A may also play a role in this loss.